Words to Avoid During Wide-awake Local Anesthesia No Tourniquet Surgery to Enhance Patient Experience - Jean Paul Brutus, MD; Natasha Barone, MDCM, MSc; Kira Stolberg, RN; Patricia Russell, RN; Donald H. Lalonde, MD, MSc, FRCSC (Plastic and Reconstructive Surgery, Global Open)
Summary:. In the evolving landscape of ambulatory surgery, wide-awake local anesthesia no tourniquet (WALANT) surgery has emerged as a preferred approach due to its efficacy, cost-effectiveness, and patient satisfaction. This paradigm shift places the patient at the center of intraoperative communication, requiring a significant change in the dialogue within the operating room (OR). Traditional conversations, which often exclude the unconscious patient, must evolve to accommodate and prioritize the psychological comfort of the conscious patient. This article examines the impact of language, tone, and conversation content on the patient experience during WALANT. We propose a communication framework that emphasizes empathy, reassurance, and patient inclusion to reduce anxiety and increase patient compliance. By analyzing common OR dialogues and their potential impact on awake patients, we identify specific phrases and words that may exacerbate patient stress or discomfort. Alternatives are suggested to foster a more positive and inclusive environment. Our recommendations are based on extensive clinical experience and supported by relevant literature, highlighting the critical role of mindful communication in improving clinical outcomes and patient satisfaction in WALANT.